Assessment of Mental Health Awareness and Accessibility of Services in the Rural Population of Sindh, Pakistan - Shagufta Haider, Faiza Memon, Ayesha Javaid, Mamoona Manzoor, Bilal Masood, Manzoor Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Mental health awareness and access to services in rural Pakistan are limited, with residents facing barriers such as stigma, financial constraints, and inadequate services, particularly in rural Sindh. Objective: This study assessed mental health awareness and service utilization among the rural population of Sindh, Pakistan. Methodology: A cross-sectional, descriptive study was conducted from September 17, 2021, and September 17, 2022, with ethical approval from the Gambat Medical College Ethical Review Committee. A simple random sampling technique recruited n=478 participants from rural districts of Sindh (Thatta, Badin, Tharparkar). Data were collected using a structured questionnaire, including sociodemographic information and mental health awareness, utilizing the Mental Health Knowledge Schedule (MAKS). Data were examined by adopting descriptive statistics as well as logistic regression in SPSS. Results: The majority of participants (81.7%) believed in medical treatments for mental illness, and 70.3% supported the availability of mental health services at the communal level. However, 80.7% reported a lack of local mental health services, with financial constraints (68.8%) and social stigma (61.1%) as major barriers. Education level and occupation significantly influenced mental health knowledge, with those having higher education and professional occupations showing greater awareness (p<0.01). Conclusion: Mental health awareness is moderate, with significant knowledge gaps, especially among those with lower education. Barriers such as financial constraints and stigma hinder service utilization, highlighting the need for community-based mental health services and educational initiatives in rural Sindh. Keywords: mental health awareness, rural population, Sindh, mental health services, barriers